Systemic risks for investments under global uncertainty - Karp, Victoria; Shtogrin, Kyryl (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
Under growing uncertainty and interdependence, systemic risks are essential for the effective functioning of the global financial system. Therefore, the subject of the proposed study is systemic risks for the global financial system. The goal of this work is to identify and disclose the role of systemic risks in carrying out investment activities. The article solves the following objectives: to identify and reveal key features and characteristics of systemic risks, to identify new challenges in systemic risk management, to identify new manifestations of systemic risks. To achieve the goal of the study, the following methods are used: system-structural, synergetic, method of comparative analysis, method of analysis and synthesis. The study reveals the following results. The main approaches to defining the concept of systemic risks are identified and their comparative analysis is carried out. The main approaches to measuring systemic risks and measurement criteria are identified. The differences between the concepts of systemic and systematic risk are revealed, and the mechanism of their interrelation is identified. New systemic risks in the conditions of global uncertainty are identified. The impact of the COVID-19 pandemic on systemic risks is determined. The main new types of risks and threats to financial stability in the long run are identified. The main directions of response of financial regulatory bodies to new systemic risks are determined. The main effects of the impact of measures to stimulate economic growth on the state of financial markets and investment activities are identified. The conclusions of the study are as follows. It is determined that there is no unanimous definition of systemic risk. Key features of systemic risks are identified, such as unpredictability, large-scale impact, spillover effect, impact on the real sector of the economy, etc. It is determined that when measuring systemic risk there are two problems: the measure of quantitative expression of systemic risk as a unit and the distribution of systemic risk between individual financial institutions. It is revealed that systemic risk can be a source of systematic risks. The COVID-19 pandemic, as an extraordinary macroeconomic shock, is belived to lead to new systemic risks. It is revealed that new types of systemic risks include, in particular, default risks, complexity of the macroeconomic environment, risks of sovereign financing, risk of lack of liquidity. The impact of new systemic risks on investment activities is revealed, in particular, changes in the business models of financial institutions, changes in the strategies of investment funds, lower ratings of debt securities, increasing the cost of debt financing, lack of liquidity.